2018
DOI: 10.1002/adfm.201803275
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Enhancement in Electrical Conductivity and Thermopower of n‐Type NiETT/PVDF Composite Films by Annealing

Abstract: Nickel ethenetetrathiolate (NiETT) polymers are promising n-type thermoelectric (TE) materials, but their insolubility requires the use of an inert polymer matrix to form films, which is detrimental to the TE performance. In this work, the use of thermal annealing as a post-treatment process simultaneously enhances the electrical conductivity from 6 ± 2 to 23 ± 3 S cm −1 and thermopower from −28 ± 3 to −74 ± 4 µV K −1 for NiETT/PVDF composite films. Spectroscopic characterization reveals that the underlying me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Other developments in solution processible n-type OTEs include metal-coordination compounds, specifically metal-dithiolene coordination polymers, consisting of bridging ethenetetrathiolate ligands and nickel metal centers (nickel ethenetetrathiolate, NiETT) (poly[Na(NiETT)]) have resulted in higher performing n-type OTEs with electrical conductivity of 44 S/cm and power factor of 20 µW/mK 2 [ 170 , 171 ]. Elmoughni et al demonstrated a textile-integrated TE generator consisting of both p and n-type organic semiconductors: PEDOT:PSS and poly[Na(NiETT)] respectively, stencil printed onto a knitted polyester fabric, as shown in Figure 6 [ 135 ].…”
Section: Flexible Thermoelectric Materialsmentioning
confidence: 99%
“…Other developments in solution processible n-type OTEs include metal-coordination compounds, specifically metal-dithiolene coordination polymers, consisting of bridging ethenetetrathiolate ligands and nickel metal centers (nickel ethenetetrathiolate, NiETT) (poly[Na(NiETT)]) have resulted in higher performing n-type OTEs with electrical conductivity of 44 S/cm and power factor of 20 µW/mK 2 [ 170 , 171 ]. Elmoughni et al demonstrated a textile-integrated TE generator consisting of both p and n-type organic semiconductors: PEDOT:PSS and poly[Na(NiETT)] respectively, stencil printed onto a knitted polyester fabric, as shown in Figure 6 [ 135 ].…”
Section: Flexible Thermoelectric Materialsmentioning
confidence: 99%
“…Na(NiETT) [50] Film with PVDF/DMSO 6 -28 0.5 Na(NiETT) [51] Film with PVDF/DMSO, annealed at 160 °C 48 -70 23.5…”
Section: Literature Review Of Niett and Nittomentioning
confidence: 99%
“…This allows us to perform a comparative characterization and apply the same processing and analysis methods to poly [Ni-tto] as are applied to poly[K x (Ni-ett)]. For example, since Wolfe and co-authors [17] explain the significant improvement in the thermoelectric characteristics of the polymer composite film after its annealing due to the removal of volatile impurities, we also carried out a heat treatment of the obtained polymer before the paste preparation and after the film deposition. Heat treatment of the polymer powder leads to an improvement in electrical conductivity ( [17].…”
Section: Polymer Development and Paste Preparationmentioning
confidence: 99%
“…For example, since Wolfe and co-authors [17] explain the significant improvement in the thermoelectric characteristics of the polymer composite film after its annealing due to the removal of volatile impurities, we also carried out a heat treatment of the obtained polymer before the paste preparation and after the film deposition. Heat treatment of the polymer powder leads to an improvement in electrical conductivity ( [17]. Since the value of the Seebeck coefficient of the poly[Ni-tto], both in the sample not subjected to heat treatment and after heat treatment, coincides with the value of the Seebeck coefficient of the post-annealing poly[K x (Ni-ett)] powder, this serves as additional evidence of the hypothesis that we proposed in the previous article [9]-that tetrathiooxalate is the true monomer for a polymer of this type and does not need any additional chemical converting.…”
Section: Polymer Development and Paste Preparationmentioning
confidence: 99%
See 1 more Smart Citation